PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENGANGKATAN KARYAWAN KONTRAK MENJADI KARYAWAN ORGANIK DENGAN METODE SAW PADA PT. KRAKATAU JASA LOGISTIK - Ahmad Surahmat; Korneilis Korneilis; Tubagus Dedy Fu'ady (Journal of Innovation And Future Technology (IFTECH), 2023)
An important element in a company that is highly expected is Human Resources (HR). If HR can be well organized, the company can carry out all its business processes properly. One of the ways of good HR management by using the regeneration of each employee, the appointment of contract employees to become organic employees is a form of regeneration as a successor for senior employees whose term of service will soon be over. So before the employee is declared retired, HR management must evaluate contract employees who will be promoted as organic employees to become their successors. There is no internal system to promote employees at PT. Krakatau Logistics Services, is a problem in hiring organic employees which usually takes time, effort and is very expensive. And do not yet have criteria that can be used as a benchmark for evaluating employee performance, making it difficult to make decisions. The system designed here uses the Simple Additive Weighting (SAW) method. The data collection methodologies used were observation and interviews, as well as the protoyping system development method and UML data modeling. The programming language used uses PHP. The positive impact of designing this decision support system is that the implementation of hiring contract employees to become organic employees can be done internally without the need to involve third party services.